2010
DOI: 10.1227/01.neu.0000371727.71991.64
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Treatment of Pediatric Intracranial Aneurysms

Abstract: Pediatric aneurysms require complex microsurgical techniques to achieve favorable outcomes. They leave higher rates of recurrence and de novo formation or growth than their adult counterparts, which mandates lifelong follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
95
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 14 publications
7
95
3
1
Order By: Relevance
“…Kakarla and colleagues report that approximately 62 % of pediatric UIA are symptomatic [5]. Discovery of UIA is linked to presentations with seizures, non-SAH-related headaches, or another neurological deficit approximately 40 % of the time [3,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kakarla and colleagues report that approximately 62 % of pediatric UIA are symptomatic [5]. Discovery of UIA is linked to presentations with seizures, non-SAH-related headaches, or another neurological deficit approximately 40 % of the time [3,6].…”
Section: Discussionmentioning
confidence: 99%
“…Durability is of concern when selecting an intervention in children with UIA due to the longer life expectancy [3,12,13]. Kakarla and colleagues retrospectively evaluated this question in 48 children with angiographic follow-up ranging 5-120 months and reported that both endovascular and microsurgical treatments achieved similar results in outcomes and suggested that microsurgical treatment may be equivalent to or better than endovascular treatment for conferring longterm durability and protection; however, follow-up was only reported in 54 % of cases reviewed [5]. Sanai and colleagues reported that while both treatments were fairly successful, endovascular treatment is associated with a recurrence rate of 20-40 %; therefore, microsurgical treatment may be more effective in permanently obliterating aneurysms [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…2,3,[6][7][8][9]12 In the pediatric population and traumatic aneurysms, arguments supporting clip ligation include that it represents definitive treatment of the aneurysm, allows for reconstruction of the parent vessel, and alleviates mass effect of the aneurysm by thrombectomy. 4,6 We chose open surgery for these very reasons. Moreover, we also postulated that the wall of the pseudoaneurysm was thin and coiling would risk rupture.…”
Section: Discussionmentioning
confidence: 99%
“…For surveillance and treatment of pediatric aneurysms, CTA or cerebral angiography are often performed during the acute phase. This is often followed by MRA, which is one of the best imaging modalities for pediatric aneurysms because it provides high-resolution images and is less invasive 11,12,[30][31][32] . However, MRA constructed with the time-of-flight method is strongly affected by speed of blood flow.…”
Section: Discussionmentioning
confidence: 99%